Análisis de riesgo de colocación y recuperación de cartera de la Cooperativa de Ahorro y Crédito Chibuleo ltda. de la provincia de Cotopaxi cantón Latacunga periodo del 1 de enero 31 diciembre 2015 - Caiza Pilco, Tania Soledad (2016)
This research includes information relating to the risk analysis and the recovery model of portfolio Credit Union and credit Chibuleo Ltda., because it will serve as an essential tool for the collection Department, which allowed through the comparison of products, elements variation and combination of accounts, having information about the facts concerning the work of operation and performance of the cooperative, is essential to have a recovery of the same portfolio management model have strategies for collection of overdue in order to determine the best conditions for decision-making. The methodology applied for execution consisted of collecting accurate and reliable information of the cooperative, in order to apply the procedures of financial analysis and determine the situation of liquidity, profitability and defaults that has the entity in the study period….